Dissecting the Heterogeneous Population Genetic Structure of Candida albicans: Limitations and Constraints of the Multilocus Sequence Typing Scheme - Muñoz, Marina; Wintaco, Luz Maira; Muñoz, Shirly Alexandra; Ramírez, Juan David (Frontiers in Microbiology, 2019)
Candida albicans is a fungal opportunistic pathogen of significant public health importance mainly due to the recent emergence of strains with increased aggressiveness and antifungal resistance. Here, we aimed to describe the epidemiological profiles and approximate the population structure of C. albicans by analyzing the C. albicans multilocus sequence typing (MLST) database (Calb-MLST-DB), which contains the largest publically available dataset for this species. Based on 4,318 database isolates, we confirmed the ubiquitous nature of C. albicans including a group of diploid sequence types (DSTs) obtained from Healthy individuals exclusively (taken as an indicator of lack of association with illnesses in its host), until isolates established from Non-Healthy individuals (potentially associated with pathogenic processes) and other DSTs reported in both types (Healthy and Non-Healthy). The highest number of reported DSTs was related to blood, oral and vaginal swabs (32.4%, 20.5% and 13.8%, respectively). High genetic diversity was observed in the seven housekeeping genes included in the MLST scheme, with a diverse population structure (154 clonal complexes, CCs; and a high number of singletons, n=1,074). Phylogenetic reconstruction on the concatenated alignment of these housekeeping genes for all the reported DSTs (n=3,483) was partially concordant with the CC assignment, however, an absence of bootstrap threshold supported nodes or p-distance, and the lack of association with the other epidemiological variables, evidenced the limitations of the MLST scheme. Marked genetic admixture signals were identified by STRUCTURE, with the majority being attributable to recombination events according to the RDP program results, although another type of exchange event cannot be ruled out. Our results reaffirm the genetic diversity inherent in the genes used for the MLST scheme, which are associated with the chromosomal remodeling already proposed for C. albicans. This was also corroborated with an internal validation at a micro geographical scale. Despite these results are biased due to the unavailability of considering the broad global spectrum of C. albicans isolates around the world. This suggests that the strategy used to population type this pathogen should be reevaluated to improve epidemiological monitoring of its health impact.